Use of IP networks for digital audio transmission - Capková, Michaela; Svoboda, Jaroslav; Volejníček, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This bachelor’s thesis explores the use of IP networks for digital audio transmission, focusing on application in professional broadcast environments. With the ongoing shift from traditional analog and digital point-to-point systems to more flexible and scalable options, audio over IP technologies have gained significant relevance. This thesis presents an overview of digital audio fundamentals, IP networks, and key IP audio solutions such as Dante, AES67, and MADI. The emphasis is placed on synchronization through the Precision Time Protocol (PTP) and the challenges of interoperability between different audio solutions. The practical section examines the implementation of AoIP in Czech Television’s mobile broadcasting unit DSNG46. Using five simplified network models and insights from four semi-structured interviews with engineers and crew members, the thesis analyzes how AoIP technologies influence workflow and production efficiency. The findings indicate that AoIP enables improved scalability, reduced cabling, and faster reconfiguration, making it suitable for mobile broadcast production. However, it also presents challenges in terms of system complexity, increased demand for network expertise, and potential limitations in device compatibility. Despite these drawbacks, the benefits of AoIP are evident when proper planning, training, and infrastructure are in place. The thesis concludes that AoIP represents a forward-looking solution in outside broadcasting units and highlights areas for further research and improvement.
Vedoucí práce: Jaroslav Svoboda
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses